(untitled) (MAUSAM, 1989)
An analysis of soil moisture and soil temperature variations under coconut in a humid tropical climate have been made for all seasons of the year. The soil moisture storage varies from 10cm to 24 cm for 75 to 90 cam depths for dry and wet periods respectively the canopy effect on soil temperature is in the range of 1 to 6 .Cup to 15 cm depth during dry period. Statistical relationships were established between soil moisture and soil temperature and between air and soil, temperatures. Indices of soil moisture (SMI), soil temperature (STI) and hydrothermal variations (HTI) were worked out for delineating different periods of the year for crop planning. The indices ranges from 0.37 to 1.00, 0.77 to 1.00 and 0.70 to 2.40 for SMI, STI and HTI respectively.